Preparation method and application of S-rich thienyl covalent organic polymer material
Synthesis of S-rich thienyl covalent organic polymer materials by solvothermal method solves the problem of low adsorption capacity of mercury ions in aqueous solution, achieves efficient mercury ion removal, with a maximum adsorption capacity of 170.6 mg·g-1, and provides A synthetic method that is easy to promote industrially.
Patent Information
- Application Number
- CN202411490917.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing adsorbents have low adsorption ability to mercury ions in aqueous solution and slow kinetics. The preparation process of most materials is harsh, has low repeatability, and is difficult to synthesize.
A S-rich thienyl covalent organic polymer material was synthesized by solvothermal method, and a new material with imine bonds was generated by amine aldehyde condensation reaction, which was used for adsorption and removal of mercury ions in aqueous solution.
It realizes efficient removal of mercury ions within the pH 3-7 range, with a maximum adsorption capacity of 170.6 mg·g-1. It has simple synthesis method, easy equipment to obtain, and stable material structure, which is suitable for industrial applications.
Smart Images

Figure CN119219876A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic functional materials and heavy metal adsorption, and in particular to a method for preparing a S-rich thienyl covalent organic polymer material and application of the material in adsorbing heavy metal mercury ions in aqueous solution. Background Art
[0002] Mercury is one of the most common and dangerous heavy metal elements. Due to its high toxicity, accumulation and persistence, it causes significant harm to human health and ecosystems. Mercury is widely used in the fields of chemistry, medicine, transportation and metallurgy. In particular, wastewater discharged from industries such as electroplating and batteries inevitably contains a large amount of divalent mercury ions. Mercury exists in various forms and transforms between forms through various reactions such as oxidation-reduction and methylation. Mercury ions, as the most common form in aqueous media, can be converted into highly toxic methylmercury in complex aqueous environments, which can cause irreversible damage to the human body, leading to lifelong problems and even life-threatening. Therefore, removing mercury from the environment is of great practical significance, and we also urgently need to find excellent materials with fast kinetics and high adsorption capacity to effectively repair and capture mercury ions from wastewater.
[0003] Nowadays, there are quite a lot of methods for the treatment of mercury in wastewater, including adsorption, solution extraction, ion exchange, chemical precipitation, microbial treatment, membrane separation, etc. Among the many methods for removing mercury, adsorption has attracted widespread attention due to its advantages such as simple operation, low cost, and easy regeneration. It has long been considered one of the most effective methods for removing heavy metals. So far, a variety of adsorbents have been prepared for mercury removal, including porous activated carbon, zeolite, clay, nanocomposites, metal organic frameworks, covalent organic polymers, etc. Traditional adsorbents are limited in terms of active functional groups for mercury ion recognition and binding, resulting in low adsorption capacity and slow adsorption kinetics. For example, zeolite and porous activated carbon are both the most commonly used mercury adsorbents. However, the adsorption effect of such traditional adsorbents is still far from ideal, especially their mercury capture performance in aqueous solution.
[0004] In comparison, covalent organic polymers (COPs) formed by light elements such as C, H, O, and N through strong covalent bonds have good chemical and thermal stability. The high repeatability of material synthesis, adjustable structure, and easy functionalization make them ideal materials for removing mercury from wastewater. However, the current COPs materials have a small adsorption capacity for mercury ions in aqueous solutions. Moreover, the preparation process conditions of most materials are harsh, with low repeatability and difficulty in synthesis. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and application of a S-rich thienyl covalent organic polymer material to solve the problems existing in the above-mentioned prior art. The present invention synthesizes a novel S-rich thienyl covalent organic polymer material connected by an imine bond by a simple solvothermal method and an amine-aldehyde condensation reaction, which can be effectively used for the adsorption and removal of heavy metal mercury ions in aqueous solution. The S-rich thienyl covalent organic polymer material of the present invention can remove mercury ions in the range of pH 3-7, and the maximum adsorption capacity is 170.6 mg·g -1 .
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is a S-rich thiophene-based covalent organic polymer material, the structural formula of which is as follows:
[0008]
[0009] The second technical solution of the present invention: The preparation method of the above-mentioned S-rich thiophene-based covalent organic polymer material comprises the following steps: mixing benzo[1,2-b:3,4-b':5,6-b"]trithiophene-2,5,8-tricarbaldehyde (BTT for short) and pyrazine-2,5-diazide (PQH for short) with a solvent, and then adding acetic acid to obtain a mixed solution; subjecting the mixed solution to a freeze-thaw cycle deoxygenation treatment, and then sealing and heating the solution to obtain the S-rich thiophene-based covalent organic polymer material (BTT-PQH for short).
[0010] Furthermore, the solvent is 1,3,5-trimethylbenzene (Mesitylene) and 1,4-dioxane (1,4-Dioxane).
[0011] Furthermore, the concentration of the acetic acid (HAc) is 6M.
[0012] Furthermore, the usage ratio of the benzo[1,2-b:3,4-b':5,6-b"]trithiophene-2,5,8-tricarbaldehyde, pyrazine-2,5-diazide, 1,3,5-trimethylbenzene, 1,4-dioxane and acetic acid is 0.2mmol:0.3mmol:4mL:4mL:0.8mL.
[0013] Furthermore, the heating reaction temperature is 120° C. and the time is 3 days (72 hours).
[0014] Furthermore, after mixing benzo[1,2-b:3,4-b':5,6-b"]terthiophene-2,5,8-tricarbaldehyde and pyrazine-2,5-diazide with the solvent, an operation of ultrasonic treatment for 20 minutes is included, and acetic acid is added after ultrasonic treatment for 20 minutes; and ultrasonic treatment is continued for 10 minutes after adding acetic acid.
[0015] Furthermore, the freeze-thaw cycle deoxygenation treatment of the mixed solution specifically includes: rapid freezing in liquid nitrogen and performing three freeze-thaw cycles.
[0016] The synthesis route of the above-mentioned S-rich thiophene-based covalent organic polymer material is as follows:
[0017]
[0018] The third technical solution of the present invention: Application of the above-mentioned S-rich thienyl covalent organic polymer material in the adsorption of heavy metal mercury ions in aqueous solution.
[0019] Furthermore, the adsorption conditions include: the pH value of the aqueous solution is 3-7.
[0020] Furthermore, the adsorption conditions also include: the temperature is room temperature; the concentration of mercury ions in the aqueous solution is 50 mg·L -1 The S-rich thienyl covalent organic polymer material is added to the aqueous solution at a concentration of 0.2 mg·L -1 .
[0021] The invention uses a simple solvothermal method to successfully prepare a S-rich thienyl covalent organic polymer by condensing a monomer benzo[1,2-b:3,4-b':5,6-b"]terthiophene-2,5,8-tricarbaldehyde and a monomer pyrazine-2,5-diacylhydrazide amine aldehyde. The polymer can be used as an effective adsorbent for mercury ions. The rich S / N content in the S-rich thienyl covalent organic polymer can ensure sufficient affinity for mercury, thereby achieving efficient adsorption of mercury. The invention provides a feasible method for the design and preparation of a mercury adsorbent.
[0022] The present invention discloses the following technical effects:
[0023] (1) The sulfur-rich thienyl covalent organic polymer material BTT-PQH synthesized in the present invention has a good effect on the adsorption and removal of mercury ions in aqueous solution, and can effectively remove mercury in a wide range of pH 3-7, with a maximum adsorption capacity of 170.6 mg g -1 .
[0024] (2) The synthesis method of the present invention requires simple equipment, the chemical reagents used are easy to obtain, the synthesis conditions are mild, the product structure is stable and not easy to hydrolyze (the infrared spectrum of BTT-PQH after immersion in aqueous solution for 48 hours is basically unchanged), the industrial application value is high, the practical application is effective, and it is easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 The Fourier transform infrared spectra of the monomer benzo[1,2-b:3,4-b':5,6-b"]terthiophene-2,5,8-tricarbaldehyde and the monomer pyrazine-2,5-diazidine and the covalent organic polymer material BTT-PQH of Example 1;
[0027] Figure 2 This is a scanning electron microscope (SEM) image of the covalent organic polymer material BTT-PQH prepared in Example 1, wherein (a) and (b) represent SEM images at different positions, respectively;
[0028] Figure 3 The infrared spectra of the covalent organic polymer material BTT-PQH prepared in Example 1 before and after being immersed in an aqueous solution for 48 hours;
[0029] Figure 4 is the adsorption capacity of the covalent organic polymer material BTT-PQH for mercury ions at pH 1-7;
[0030] Figure 5 It is the specific adsorption effect of the covalent organic polymer material BTT-PQH on mercury ions in the presence of multiple coexisting ions. DETAILED DESCRIPTION
[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0032] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0033] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0034] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0036] The raw materials used in the specific implementation of the present invention are all common commercial products, among which the structural formula of BTT is The CAS number is 2243590-42-1; the structural formula of pyrazine-2,5-dihydrazide is The CAS number is 46321-76-0.
[0037] The room temperature involved in the specific implementation manner of the present invention specifically refers to 20-30°C.
[0038] Example 1
[0039] A method for preparing a S-rich thiophene-based covalent organic polymer material, comprising the following steps:
[0040] The monomer BTT (66.1 mg, 0.2 mmol) and pyrazine-2,5-dihydrazide (58.8 mg, 0.3 mmol) were added to a 25 mL Schlenk tube, and then solvents 1,3,5-trimethylbenzene (4 mL) and 1,4-dioxane (4 mL) were added. After 20 min of ultrasonic treatment, a completely uniform mixture was obtained, and then 0.8 mL of 6M acetic acid was added and ultrasonic treatment was continued for 10 min to obtain a mixed solution. The Schlenk tube was then quickly frozen in liquid nitrogen, deoxygenated through three freeze-thaw cycles, and sealed, and reacted at 120 ° C for 3 (72 h) days without interference. After the reaction was completed, it was cooled to room temperature, the material was collected by filtration, and washed with methanol, tetrahydrofuran, water, and ethanol respectively. Finally, the collected washed material was dried in a vacuum oven at 60 ° C for 12 h to obtain a S-rich thienyl covalent organic polymer material (referred to as BTT-PQH) with a yield of 71% (89 mg).
[0041] Test Example 1
[0042] Morphology and structure characterization of covalent organic polymer materials
[0043] Figure 1 The Fourier transform infrared spectra of the monomer benzo[1,2-b:3,4-b':5,6-b"]terthiophene-2,5,8-tricarbaldehyde and the monomer pyrazine-2,5-diacylhydrazine and the covalent organic polymer material BTT-PQH of Example 1 are shown in FIG. Figure 1 In the infrared spectrum of BTT-PQH, CHO (1656 cm -1 ) characteristic peaks and the obvious weakening of -NH 2 (3000–3300cm -1 ) characteristic peak disappears. In addition, the peak at 1599cm -1 An obvious new peak appears at , which is attributed to the vibration stretching band of the imine bond (C=N), indicating the successful formation of the polymer.
[0044] Figure 2 This is a scanning electron microscope image of the covalent organic polymer material BTT-PQH prepared in Example 1, wherein (a) and (b) represent SEM images at different positions, respectively. Figure 2 It can be seen that the morphology of BTT-PQH is formed by the stacking of many small nanoparticles.
[0045] Figure 3 The infrared spectra of the covalent organic polymer material BTT-PQH prepared in Example 1 before and after being immersed in an aqueous solution for 48 hours are shown in FIG. Figure 3 It can be seen that the infrared spectrum of BTT-PQH after being immersed in aqueous solution for 48 hours has basically no change, proving that its structure is stable and not easily hydrolyzed.
[0046] Test Example 2
[0047] Test of the adsorption performance of covalent organic polymer materials for mercury ions
[0048] Test method:
[0049] 1. Effect of pH: At room temperature, in 50mL of initial mercury ions (Hg 2+ ) concentration is 50 mg·L -1 10 mg of BTT-PQH adsorbent (prepared in Example 1) was added to the mercury solution for adsorption. After reaching adsorption equilibrium, the solution was filtered with a 0.22 μm filter head, and 2 mL of the clear solution was taken and diluted and analyzed by ICP-MS for Hg in the filtered solution. 2+ The adsorption capacity of BTT-PQH for mercury ions in different pH environments was calculated based on the residual content.
[0050] 2. Competitive adsorption experiment: The initial concentration of each metal ion was 100 mg·L by directly dissolving hydrochloride or nitrate in water. -1 Mixed metal ion solution (Hg 2+ Mg 2+ 、Al 3+ , Mn 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ , Sr 2+ 、Cd 2+ , Cs 2+ ,La 3+ 、Eu 3+ , Gd 3+ 、Dy 4+ , Pb 2+ The concentration was 100 mg·L -1 ), and then diluted to a concentration of 10 mg / L for each metal ion before use. -1 , and the pH was adjusted to 6. 10 mg of BTT-PQH adsorbent (prepared in Example 1) was added to the mixed metal ion solution at pH = 6 for adsorption. After reaching adsorption equilibrium, it was filtered with a 0.22 μm filter head, and 2 mL of the clear solution was taken. After dilution, the residual content of each metal ion in the filtered solution was analyzed by ICP-MS, and the removal rate of each metal ion by BTT-PQH was calculated.
[0051] Test results: Figure 4 is the adsorption capacity of BTT-PQH for mercury ions at pH 1-7, Figure 4It can be seen that BTT-PQH can effectively remove mercury in a wide range of pH 3-7, with a maximum adsorption capacity of 170.6 mg g -1 . Figure 5 The adsorption effect of BTT-PQH on mercury ions in the presence of multiple coexisting interfering ions. Figure 5 It can be seen that BTT-PQH can 2+ Specific adsorption was performed, and in the presence of 15 coexisting interfering ions, the removal rate of mercury by BTT-PQH was 78.5%, showing excellent anti-interference ability.
[0052] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A S-rich thiophene-based covalent organic polymer material, characterized in that: The structural formula is as follows:
2. The method for preparing the S-rich thienyl covalent organic polymer material according to claim 1, characterized in that: The following steps are involved: Benzo[1,2-b:3,4-b':5,6-b"]terthiophene-2,5,8-tricarbaldehyde and pyrazine-2,5-diazidine are mixed with a solvent, and then acetic acid is added to obtain a mixed solution; the mixed solution is subjected to a freeze-thaw cycle deoxygenation treatment, and then sealed and heated for reaction to obtain the S-rich thienyl covalent organic polymer material.
3. The preparation method according to claim 2, characterized in that: The solvents are 1,3,5-trimethylbenzene and 1,4-dioxane.
4. The preparation method according to claim 2, characterized in that: The concentration of the acetic acid is 6M.
5. The preparation method according to claim 3, characterized in that: The dosage ratio of the benzo[1,2-b:3,4-b':5,6-b"]trithiophene-2,5,8-tricarbaldehyde, pyrazine-2,5-diazide, 1,3,5-trimethylbenzene, 1,4-dioxane and acetic acid is 0.2mmol:0.3mmol:4mL:4mL:0.8mL.
6. The preparation method according to claim 2, characterized in that: The heating reaction was carried out at a temperature of 120° C. for 3 days.
7. Use of the S-rich thienyl covalent organic polymer material according to claim 1 in the adsorption of heavy metal mercury ions in aqueous solution.
8. The use according to claim 7, characterized in that The adsorption conditions include: the pH value of the aqueous solution is 3-7.
Citation Information
Patent Citations
Benzotrithienyl covalent organic framework catalyst as well as preparation method and application thereof
CN115463687A
Donor-acceptor type S atom doped two-dimensional covalent organic framework material, preparation method and application of donor-acceptor type S atom doped two-dimensional covalent organic framework material in photocatalytic nitrogen fixation
CN118638287A
Thiophene-based imine-linked covalent organic framework for iodine adsorption
CN118667105A